2016
DOI: 10.1128/iai.01330-15
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Phenol-Soluble Modulins Impair Interleukin Expression in Bovine Mammary Epithelial Cells

Abstract: iThe role of the recently described interleukin-32 (IL-32) in Staphylococcus aureus-induced mastitis, an inflammation of the mammary gland, is unclear. We determined expression of IL-32, IL-6, and IL-8 in S. aureus-and Escherichia coli-infected bovine mammary gland epithelial cells. Using live bacteria, we found that in S. aureus-infected cells, induction of IL-6 and IL-8 expression was less pronounced than in E. coli-infected cells. Notably, IL-32 expression was decreased in S. aureus-infected cells, while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The MOI was based on pilot experiments that demonstrated that at this multiplicity, PS cells have the strongest IL-8 response to S. aureus in the absence of cytotoxic effects, as assessed by trypan blue staining and microscopy examination. The same maximum MOI for stimulating PS cells with S. aureus was also found by Deplanche et al [28]. After three hours, bacteria were removed by washing cells two times with PBS, followed by incubation in 0.5 mL SM containing 100 µg/mL streptomycin and 100 I.U./mL penicillin to prevent growth of bacteria.…”
Section: Ps Cell Responses To S Aureussupporting
confidence: 67%
“…The MOI was based on pilot experiments that demonstrated that at this multiplicity, PS cells have the strongest IL-8 response to S. aureus in the absence of cytotoxic effects, as assessed by trypan blue staining and microscopy examination. The same maximum MOI for stimulating PS cells with S. aureus was also found by Deplanche et al [28]. After three hours, bacteria were removed by washing cells two times with PBS, followed by incubation in 0.5 mL SM containing 100 µg/mL streptomycin and 100 I.U./mL penicillin to prevent growth of bacteria.…”
Section: Ps Cell Responses To S Aureussupporting
confidence: 67%
“…For example, in conjunctiva epithelial cells, a significant increase in IL-8 mRNA was detected at 3 h post infection and a marked reduction after 4 h, an effect attributed to phenol-soluble modulins from S. aureus ( 45 ). Also, bovine mammary epithelial cells infected with S. aureus expressed IL-8 at initial stages (8 h), but at longer infection times (24–48 h), no increase was detected ( 46 ). In neutrophils, S. aureus strain USA300 inhibited NF-κB-dependent IL-8 expression and promoted cell death ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus produces phenol-soluble modulins (PSMs) as virulence factors, which have potent cytolytic activity against many cell types, including neutrophils and monocytes. Furthermore, PSMs decrease the expression of several defensin genes in epithelial cells and inhibit the production of IL-6, IL-8 and IL-32 in bovine MECs, resulting in attenuation of antibacterial function [ 3 ]. These components of S. uberis and S. aureus may prevent the bacteria from being attacked by immune cells and antimicrobial components.…”
Section: Discussionmentioning
confidence: 99%